1982
DOI: 10.1055/s-0038-1657125
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Functional Study of Antithrombin III in Newborn Infants

Abstract: SummaryAntithrombin III (AT-III) was isolated by heparin affinity chromatography from adult venous and newborn term and preterm umbilical cord blood. The purified proteins were compared by SDS-PAGE, rocket immuno-electrophoresis, protein concentration by microbiuret relative to optical density at 280 nm, heparin cofactor specific activity, progressive neutralization of thrombin and factor Xa at 37°C and pH related antithrombin kinetics. The structural evaluations revealed a fetal AT-III of molecular weight, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…Levels of AT-111 increase with increasing gestational age and postnatal age in healthy infants achieving values in the lower adult range as early as at 1 wk of age (3,16). AT-111 from both premature and full term cord blood has been isolated and is identical to AT-I11 from adults with respect to a variety of functional and immunologic properties thus excluding the possibility of a fetal form of AT-111 (16,21). This study confirms those reports; however, we observed a dysfunctional AT-111 molecule later in the postnatal period in a select population of sick premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of AT-111 increase with increasing gestational age and postnatal age in healthy infants achieving values in the lower adult range as early as at 1 wk of age (3,16). AT-111 from both premature and full term cord blood has been isolated and is identical to AT-I11 from adults with respect to a variety of functional and immunologic properties thus excluding the possibility of a fetal form of AT-111 (16,21). This study confirms those reports; however, we observed a dysfunctional AT-111 molecule later in the postnatal period in a select population of sick premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…12,28 This study, which employed chromogenic microanalytic techniques, has confirmed previous reports of a significant reduction (35-45%) in the levels of antithrombin III, plasminogen, 2,4,7,15,31 and protein C 7,13 in neonates compared with adults; no such differences were noted in the levels of alpha2-antiplasmin. Recent evidence has also shown that fetal and adult antithrombin possess the same molecular weight, charge, and electrophoretic migration pattern, 16,30 and therefore newborns display a quantitative and not qualitative deficiency of antithrombin. The low neonatal levels of the hemostatic inhibitors, antithrombin III, and protein C, but not alpha2-antiplasmin, are in the range defined for thromboembolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The data, which represent the reference values for Saudi neonates, are compared in Table 2 with similar data from other ethnic populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of complexes of procoagulant proteins with AT is accelerated 1000-fold by heparin (12). Newborn infants have been shown to have approximately 50% adult plasma concentration of a functionally normal AT (6,13). Heparin resistance, or failure to achieve a plasma anti-Xa activity commensurate with therapeutic heparin infusion rate, is commonly found in infants and ascribed to low neonatal levels of AT (14 -16).…”
mentioning
confidence: 99%